Quantification of biologically active DNA alkylation in temozolomide-exposed glioblastoma cell lines by ultra-performance liquid chromatography-tandem mass spectrometry: method development and recommendations for validation - Fresnais, Margaux; Jung, Ina; Klein, Uli; Theile, Dirk; Liang, Siwen; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (ACS omega, 2023)
Quantitative monitoring of biologically active methylations of guanines in samples exposed to temozolomide (TMZ) would be useful in glioblastoma research for preclinical TMZ experiments, for clinical pharmacology questions regarding appropriate exposure, and ultimately for precision oncology. The known biologically active alkylation of DNA induced by TMZ takes place on O6 position of guanines. However, when developing mass spectrometric (MS) assays, the possible signal overlap of O6-methyl-2′-deoxyguanosine (O6-m2dGO) with other methylated 2′-deoxyguanosine species in DNA and methylated guanosines in RNA must be considered. Liquid chromatography-tandem MS (LC-MS/MS) offers the analytical requirements for such assays in terms of specificity and sensitivity, especially when multiple reaction monitoring (MRM) is available. In preclinical research, cancer cell lines are still the gold standard model for in vitro drug screening. Here, we present the development of ultra-performance LC-MRM-MS assays for the quantification of O6-m2dGO in a TMZ-treated glioblastoma cell line. Furthermore, we propose adapted parameters for method validation relevant to the quantification of drug-induced DNA modifications.